2019
DOI: 10.5152/tjg.2019.18534
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic efficacy of serum procalcitonin, IL-6, IL-2, and D-dimer levels in an experimental acute appendicitis model

Abstract: Background/Aims: Acute appendicitis is the most frequent cause of acute abdomen emergency surgery. It continues to be a problem today due to delayed diagnosis and its high perforation rate. For this reason, diagnostic tests continue to be developed. In this experimental study, the diagnostic significance of blood procalcitonin (PCT), interleukin (IL)-6, IL-2, and D-dimer levels in an acute appendicitis model in rabbits was investigated. Materials and Methods: A total of five groups were included: control group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…Numerous parameters have been examined to support the diagnosis of acute appendicitis until today. CRP, IL-6, tumor necrosis factor, procalcitonin (PCT), granulocyte colony-stimulating factor, calprotectin, chemokine ligand-8, serum amyloid A, matrix metalloproteinase 9, and myeloperoxidase are among the inflammatory markers investigated to support diagnosis [8,[12][13][14]. However, in some cases, none of the new inflammatory markers, including leukocyte, C-reactive protein (CRP), or PCT, can identify acute appendicitis with high specificity and sensitivity [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous parameters have been examined to support the diagnosis of acute appendicitis until today. CRP, IL-6, tumor necrosis factor, procalcitonin (PCT), granulocyte colony-stimulating factor, calprotectin, chemokine ligand-8, serum amyloid A, matrix metalloproteinase 9, and myeloperoxidase are among the inflammatory markers investigated to support diagnosis [8,[12][13][14]. However, in some cases, none of the new inflammatory markers, including leukocyte, C-reactive protein (CRP), or PCT, can identify acute appendicitis with high specificity and sensitivity [13].…”
Section: Introductionmentioning
confidence: 99%
“…CRP, IL-6, tumor necrosis factor, procalcitonin (PCT), granulocyte colony-stimulating factor, calprotectin, chemokine ligand-8, serum amyloid A, matrix metalloproteinase 9, and myeloperoxidase are among the inflammatory markers investigated to support diagnosis [8,[12][13][14]. However, in some cases, none of the new inflammatory markers, including leukocyte, C-reactive protein (CRP), or PCT, can identify acute appendicitis with high specificity and sensitivity [13]. PCT, Interleukin (IL)-6, IL-2, and D-dimer plasma levels are elevated at different levels in the course of acute appendicitis and may be of particular value in the diagnosis of acute appendicitis [13].…”
Section: Introductionmentioning
confidence: 99%
“…IL-6 is a proinflammatory cytokine, mediator of acute phase reaction, and is secreted during inflammatory process and neutrophil recruitment following the invasion of bacteria to the appendix [14,15]. Some of the previous studies have shown its relatively high sensitivity (73-84%) and low specificity (46-72%) for diagnosing AA and even higher sensitivity (up to 91%) and lower specificity (37%) for diagnosing perforated appendicitis [16,17]. Elevated serum IL-6 levels were found in the majority of our patients (55, 82.09%, p < 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…When both tests were concomitantly evaluated, the sensitivity and specificity values were 95% and 55%, respectively. It was reported that Pct and IL-6 are more efficient predictors of AA than IL-2 and D-dimer [23]. Our main aim when planning the study was to investigate the relationship between Pct and IL-6 levels and SUVmax values by acquiring blood samples at the same time with 68 Ga-citrate PET/CT imaging times.…”
Section: Discussionmentioning
confidence: 99%
“…However, the contribution of other acute-phase reactants, such as D-dimer, IL-2, IL-6 and Pct to AA diagnosis has also been investigated. For instance, Pct, IL-6, IL-2 and D-dimer plasma levels are elevated during the course of AA [21][22][23].…”
Section: Gallium-68 Citrate Pet/ct Findings In An Experimental Model mentioning
confidence: 99%